Regressed retinopathy of prematurity in children aged 5-8 years in Sivas, Turkey - Ergür, Özkan; Törel Ergür, Ayça; Güler, Cenap (The Turkish Journal of Pediatrics, 2000)
In this present study regressed retinopathy of prematurity has been investigated in children born prematurely (< 2300 g birth weight and < 34 weeks gestational age) in Sivas, Turkey during January 1989-January 1992. At the age of 5-8 years, 55 children born prematurely were examined; eye fundus information could be obtained by indirect ophthalmoscopy in all of them. The frequency of regressed retinopathy of prematurity was 35.45 percent for the whole group. Severe forms with optic atrophy, dragged optic disk, vitreoretinal scarring, retinal traction and temporal avascular retina were seen in 13.63 percent of cases. Moderate forms with pigmentary changes, vitreoretinal interphase changes and lattice degeneration were seen in 21.81 percent of cases. While the severe and moderate regressed premature retinopathy findings in premature children with gestational ages of 30-34 weeks were observed to be 12.0 and 14.0 percent, respectively, those in the 25-29 week-gestational-aged premature children were determined to be 5.0 and 28.33 percent, respectively. Although the incidence of both severe and moderate regressed premature retinopathy was higher in the 25-29 week gestational-aged group when compared to that of the 30-34-week-gestational-aged group, the difference was not found to be statistically significant (p > 0.05). In conclusion, premature retinopathy should not only be followed up in the early stage with active changes but also later in infancy and childhood because of regressed premature retinopathy findings that may require treatment.